Carcass And Wholesalecut Production Of Brahman Cross (BX) Heifer - Kuswati Kuswati; Abdul Muhaimin; Wike Andre Septian; Trinil Susilawati (Jurnal Ilmu dan Teknologi Hasil Ternak (JITEK), 2022)
This research aims to determine the quantitative characteristics of Brahman cross heifer cattle's carcass and wholesale cut at different age levels. The number of heifer cattle taken as samples was 104 heifer. The research method used is a case study with the selection of locations by purpose sampling. Direct observation is used to obtain information on age, slaughter weight, carcass weight, wholesale cut weight, and parts thereof (primary, secondary, and manufacturing cut). The data obtained were then analyzed by analysis of variance (ANOVA). If there was a significant difference, it is followed by a further test of the Least Significant Difference (LSD). The results showed that the age levels in slaughter had a significant effect (P<0.05) on the slaughter weight, fresh carcass weight and wilted carcass weight, but had no effect on the percentage of carcass and wholesale cut. The older the age of cattle and the longer the cattle are raised, the higher their body weight will affect the slaughter weight produced, and the higher the slaughter weight, the higher the carcass weight made. Average slaughter weight at different age by Permanent Incisor (PI): PI0 (<18 months), PI2 (18-24 months) and PI4 (24- 36 months). While the average percentage of heifer carcass at different age levels was relatively the same (52,71% : 53,04% : 53.10%). The weight and rate of wholesale cut and its parts are also somewhat the same. The research results show that the slaughter age affects the slaughter weight and carcass weight but not dressing percentage and wholesale cut weight. Brahman cross heifer cattle at PI4 produced optimal carcass weight and wholesale cut.